Thermal Performance Monitoring and Optimization in Nuclear Power Plants : Experience and Lessons Learned. (IAEA-TECDOC, 2021)
"Rising operating costs and increased competition have focused attention on the need to improve thermal performance in nuclear power plants (NPPs), to ensure efficient electricity generation. Efforts to improve thermal performance require a broad understanding of NPP design, operation, maintenance, ambient conditions, and thermal sciences. This publication provides various methodologies for tracking and trending NPP thermal performance. It describes the essential elements of a thermal performance programme, providing guidelines on the design of the balance of the plant systems for new build NPPs and improvements to an existing programme for operating NPPs."--Publisher's description.